THE APPLICATION OF ASSEMBLR STUDIO LEARNING MEDIA TO LEARNING OUTCOMES IN SOCIAL STUDIES SUBJECTS FOR GRADE VIII STUDENTS OF SINAR HUSNI JUNIOR HIGH SCHOOL: PENERAPAN MEDIA PEMBELAJARAN ASSEMBLR STUDIO TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPS SISWA KELAS VIII SMP SINAR HUSNI - Diana Agustina; Ponidi Ponidi (SOSIOEDUKASI, 2025)
Assemblr Studio is a learning media application that is currently being developed for educational purposes in creating or designing 3D animations that are fun and interactive. With the help of this 3D technology, it can encourage students to learn and understand learning. Learning outcomes are an important point that should not be missed in the learning and teaching process because it is the most visible indicator of learning achievement. This study uses a quantitative research approach method with the type of True Experimental Design research (experimental design) and the form of Pretest-Posttest Control Group Design research, namely experiments carried out in two groups with a quantitative approach. The purpose of this study is to find out how the learning outcomes of students taught using Assemblr Studio Learning Media affect student learning outcomes in the Social Studies subject of class VIII SMP Sinar Husni and whether there is an influence of Assemblr Studio learning media on student learning outcomes in the Social Studies subject of class VIII SMP Sinar Husni. Data were analyzed using SPSS version 26. The results of the analysis concluded that there is a significant influence of Assemblr Studio learning media on learning outcomes in the Social Studies subject of class VIII SMP Sinar Husni.